Advances in Dementia Research (IntechOpen, 2023)
Advances in Dementia Research provides a comprehensive overview of Alzheimer's dementia. This book also represents the association between the components of metabolic syndrome and Alzheimer's disease. Vascular dementia associated with neurodegeneration and cognitive impairments is due to multiple complications of the neurovascular system. This book attempts to explore the recent advancements of enzyme targets for the management of vascular dementia. Furthermore, this book highlights the effectiveness of social recreational programs as an example of a recovery intervention for persons with dementia that focuses on reducing the risk of social isolation associated with dementia. Together the insightful research presented in this book provides valuable information for neuroscientists, researchers, medical professionals, academicians, and upper-level students, as well as for industry professionals.